Empowerment As a Trojan Horse: New Systems of Work Organization in the North American Automobile Industry - Yates, Charlotte A. B. (Charlotte Alyce Bronwen); Lewchuk, Wayne; Stewart, Paul (Economic and Industrial Democracy, 2001)
While new models of work organization (lean production) in the automobile industry have been portrayed as a 'democratic' break with Fordism, we find considerable parallels with those traditional patterns of labour control they were intended to supplant. Far from understanding these as exemplars of 'democratic Taylorism', the article identifies specific company responses to problems associated with declining productivity and competitiveness. Moreover, the article argues that new models of work organization associated with lean production, far from heralding empowerment, are more conerned with asserting management control in varying ways in different companies.

Abstracts = Résumés [47, Spring 2001] (Labour/Le Travail, 2001)
English/French abstracts of the articles in the Spring 2001 volume.

Abstracts = Résumés [48, Fall 2001] (Labour/Le Travail, 2001)
English/French abstracts of the articles in Fall 2001 volume.

Index, Volume 45-46, 2000 (Labour/Le Travail, 2001)
Biennial index produced by the Canadian Periodical Index.

Livres reçus (Relations industrielles / Industrial Relations, 2001)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications: Committee on Canadian Labour History (Labour/Le Travail, 2001)
Advertisement for the journal, Labour/Le Travail.

Publications récentes (Relations industrielles / Industrial Relations, 2001)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

On the Convergence of Labour Rights and Human Rights - Adams, Roy J. (Relations industrielles / Industrial Relations, 2001)
This article discusses Unfair Advantage: Workers' Freedom of Association in the United States under International Human Rights Standards and Your Voice at Work: Global Report under the Follow-up to the ILO Declaration on Fundamental Principles and Rights at Work. During the past decade a strong international consensus has emerged that holds that a set of core labor rights should be regarded as fundamental human rights. The appearance of these 2 reports indicates that the situation is rapidly changing.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employees; Freedom of Association; Globalization; HUMAN rights; Labor Unions; Labor relations; Research; Rights; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

So Close to the State/s: The Emergence of Canadian Feature Film Policy - Adria, Marco (Labour / Le Travail, 2001)
The article reviews the book, "So Close to the State/s: The Emergence of Canadian Feature Film Policy," by Michael Dorland.

Report from Cannes 2000 - Armstrong, Lawrin (Labour / Le Travail, 2001)
The article reviews the following laobur/left films that were screened at the Cannes 2000 festival: "Bread and Roses." UK, directed by Ken Loach; "Takhté Siah" (Blackboards). Iran, directed by Amira Makhmalbaf; "Lista de Espéra" (Waiting List). Spain/Cuba, directed by Juan Carlos Tabio; "Capitaes de Abril" (Captains of April), Portugal, directed by Maria de Medeiros.

Workplace Innovations in Large, Unionized Canadian Organizations - Balkin, David B.; Tremblay, Michel; Westerman, James (Journal of Business and Psychology, 2001)
The study reports workplace innovations in 112 large, unionized Canadian organizations from data collected in 1994 by the Bureau of Labour Information. The frequency of specific workplace innovations and the relationship to organization and bargaining unit characteristics are reported.
https://link.springer.com/article/10.1023/A:1007822717297

Pierre Elliot Trudeau, 1919-2000: The Death of Canadian Liberalism - Barsallo, Alicia (Labour / Le Travail, 2001)
The article pays tribute to Trudeau and the standard of political discourse he represented.

A Theory of Employment Systems : Micro-Foundations of Societal Diversity - Bélanger, Jacques (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "A Theory of Employment Systems : Micro-Foundations of Societal Diversity," by David Marsden.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment; History; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Nice Girls and Rude Girls: Women Workers in World War One; Working Class Cullture, Women and Britain, 1914-1921 - Bell, Amy (Labour / Le Travail, 2001)
The article reviews the books, "Nice Girls and Rude Girls: Women Workers in World War One," by Deborah Thom, and "Working Class Cullture, Women and Britain, 1914-1921," by Claire A. Culleton.

Ergonomie, formation et transformation des milieux de travail: introduction - Bellemare, Marie; Montreuil, Sylvie (Relations industrielles / Industrial Relations, 2001)
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Ergonomics; Labor Unions; Occupational health & safety; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Training

L'amelioration des situations de travail par l'ergonomie participative et la formation - Bellemare, Marie; Montreuil, Sylvie; Marier, Micheline; Allard, Denis (Relations industrielles / Industrial Relations, 2001)
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Ergonomics; Injuries; Labor Unions; Musculoskeletal system; Occupational health & safety; Participatory research; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Training

L’amélioration des situations de travail par l’ergonomie participative et la formation - Bellemare, Marie; Montreuil, Sylvie; Marier, Micheline; Prévost, Johane; Allard, Denis (Relations industrielles / Industrial Relations, 2001)
Cet article présente la démarche et l’évaluation d’une intervention participative fondée sur une formation dispensée auprès de groupes Ergo réunissant des cadres et des employés du secteur de la production de métal chaud. La formation portait d’abord sur le diagnostic ergonomique et puis sur la transformation des situations de travail. L’évaluation de type réaliste porte sur le processus et les résultats. Elle montre que la concrétisation des projets d’amélioration dans les usines implique certes des acquis relatifs à l’analyse du travail obtenus par la formation, mais aussi que les participants à la formation détiennent ou développent une connaissance riche des processus de conduite de projets — formels et informels — propres à l’usine.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Gestion de la rémunération : théorie et pratique - Bernier, Jean (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Gestion de la rémunération : théorie et pratique," by Roland Thériault and Sylvie St-Onge.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Compensation administration; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Recherche évaluative d’un programme syndical de formation en santé et en sécurité du travail - Berthelette, Diane; Desnoyers, Luc; Bédard, Anne (Relations industrielles / Industrial Relations, 2001)
L’objectif de cette recherche évaluative était d’analyser la relation susceptible d’exister entre le processus d’un programme de formation de base en santé et sécurité du travail et ses effets attendus. Ce programme, dispensé par une centrale syndicale québécoise à ses membres, a pour objectif ultime d’améliorer l’action syndicale des travailleurs à ce sujet dans leur milieu de travail. Nos résultats semblent indiquer que ce programme produit la majorité des effets attendus relatifs aux thèmes étudiés, soit d’accroître la compréhension du rôle des facteurs environnementaux sur l’occurrence d’accidents de travail et d’attribuer ces événements à des risques environnementaux dont les employeurs sont responsables.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Public Sector Labour Relations in an Era of Restraint and Restructuring - Boivin, Jean (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Public Sector Labour Relations in an Era of Restraint and Restructuring," by Gene Swimmer.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; Public sector; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Restructuration industrielle et action syndicale locale: Le cas de l’industrie du papier au Québec - Bourque, Reynald; Rioux, Claude (Relations industrielles / Industrial Relations, 2001)
La restructuration de l’industrie du papier au Québec a eu un impact majeur sur l’action syndicale. Cet article présente les changements intervenus dans les pratiques syndicales de la Fédération des travailleurs du papier et de la forêt (FTPF-CSN) et de ses syndicats affiliés, notamment en ce qui a trait à la demande de nouveaux services découlant de l’implication syndicale dans la réorganisation du travail. Nous analysons également les effets de ces changements sur les relations entre la FTPF et ses syndicats locaux, ainsi que les problèmes et les défis inhérents au renouvellement des pratiques syndicales.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

"Rights, not Roses": Unions and the Rise of Working-Class Feminism, 1945-80 - Brooks, Tequila J. (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Rights, not Roses": Unions and the Rise of Working-Class Feminism, 1945-80," by Dennis A. Deslippe.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Feminism; History; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Abandoned Children - Brown, Helen (Labour / Le Travail, 2001)
The article reviews the book, "Abandoned Children," edited by Catherine Panter-Brick and Malcolm T. Smith.

Turning Trees into Dollars: The British Columbia Coastal Lumber Industry 1858-1913 - Bunting, Robert (Labour / Le Travail, 2001)
The article reviews the book, "Turning Trees into Dollars: The British Columbia Coastal Lumber Industry, 1858-1913," by Gordon Hak.

Rum Punch and Revolution: Taverngoing and Public Life in Eighteenth-Century Philadelphia - Campbell, Robert A. (Labour / Le Travail, 2001)
The article reviews the book, "Rum Punch and Revolution: Taverngoing and Public Life in Eighteenth-Century Philadelphia," by Peter Thompson.

The Power to Choose: Bangladeshi Women and Labour Market Decisions in London and Dhaka - Caspersz, Donella (Relations industrielles / Industrial Relations, 2001)
The Power to Choose: Bangladeshi Women and Labour Market Decisions in London and Dhaka, by Naila Kabeer, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Clothing industry; Employees; Employment; LABOR market; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Women

Norman Feltes, 1932-2000: An OCAP Appreciation - Clarke, John (Labour / Le Travail, 2001)
The article pays tribute to Norman Feltes's contribution to the Ontario Coalition Against Poverty after his retirement as an English professor.

More with Less: Work Reorganization in the Canadian Mining Industry - Clement, Wallace (Labour / Le Travail, 2001)
The article reviews the book, "More with Less: Work Reorganization in the Canadian Mining Industry," by Bob Russell.

The Agribusiness Threat to Farmers, Food, and the Environment - Conway, J. F. (Labour / Le Travail, 2001)
The article reviews the book, "The Agribusiness Threat to Farmers, Food, and the Environment," edited by Fred Magdoff, John Bellamy Foster, and Frederick H. Butt.

William Z. Foster and the Tragedy of American Radicalism/Second String Red: The Life of Al Lannon, American Communist - Cotterill, Steven (Labour / Le Travail, 2001)
The article reviews the book, "William Z. Foster and the Tragedy of American Radicalism," by James R. Barrett.

A Thing of the Past? Child Labour in Britain in the Nineteenth and Twentieth Centuries - Coulter, Rebecca Priegert (Labour / Le Travail, 2001)
The article reviews the book, "A Thing of the Past? Child Labour in Britain in the Nineteenth and Twentieth Centuries," edited by Michael Lavalette.

Solidarité et détermination. Histoire de la Fraternité des policiers et des policières de la Communauté urbaine de Montréal - Dagenais, Michèle (Labour / Le Travail, 2001)
The article reviews the book, "Solidarité et Détermination: Histoire de la Fraternité des Policiers et des Policières de la Communauté Urbaine de Montréal," by Jacques Rouillard and Henri Goulet.

La présence communiste au Québec (1929-1939) ou la présence de « l'homme au couteau entre les dents » - Dansereau, Bernard (Bulletin d'histoire politique, 2001)
Examines the presence and struggles of the Communist Party of Canada (le Parti communiste canadien (PCC)) in Quebec during the 1930s. It highlights the challenges faced by the PCC, including widespread anticommunism from the government, the Catholic Church, and conservative labour unions. The PCC sought to organize workers through independent unions like the Workers Unity League and engaged in social struggles, including unemployment protests and antifascist campaigns. Despite some successes in labour movements and antifascist efforts, the PCC failed to become a mass party, remaining largely isolated and marginalized, especially among francophone workers. The article also discusses the PCC's strategic shifts, from ultra-revolutionary rhetoric to a united antifascist front, and its eventual decline during World War II. Overall, the PCC's efforts were significant in challenging capitalism and advocating for workers' rights, but its influence remained limited in Quebec's political and social landscape.

Nonunion Employee Representation: History, Contemporary Practice, and Policy - Debicki, Christopher (Relations industrielles / Industrial Relations, 2001)
Nonunion Employee Representation: History, Contemporary Practice, and Policy, edited by Bruce E. Kaufman and Daphne Gottlieb, is reviewed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; History; Labor Unions; Labor relations; Nonunion; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Recherche evaluative d'un programme syndical de formation en sante et en securite du travail - Desnoyers, Luc; Berthelette, Diane; Bedard, Anne (Relations industrielles / Industrial Relations, 2001)
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Industrial accidents; Labor Unions; Occupational health & safety; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Training

Women and Scientific Employment - Dodd, Janice G. (Labour / Le Travail, 2001)
The article reviews the book, "Women and Scientific Employment," by Judith Glover.

"Our Mickey": The Story of Private James O'Rourke, VC.MM (CEF), 1879-1957 - Dooley, Michael Kevin (Labour / Le Travail, 2001)
Discusses the life of Michael James "Mickey" O'Rourke, miner, soldier, and labour activist. In 1917, he was awarded Canada's highest military decoration, the Victoria Cross, for "conspicuous bravery and devotion to duty during prolonged operations" while a member of the 7th Battalion of the Canadian Expeditionary Force during World War I. After the war O'Rourke went to California, then returned to British Columbia where he played a prominent role in the 1935 Vancouver longshoremen's strike. Despite chronic health problems that were war-related, he received only a small pension as a disabled veteran. O'Rourke's later life was complicated by alcoholism. He died as an indigent at a Veterans' Affairs facility in Burnaby, British Columbia, in 1957.

The Challenge of Global Capitalism: The World Economy in the 21st Century - Drache, Daniel (Labour / Le Travail, 2001)
The article reviews the book, "The Challenge of Global Capitalism: The World Economy in the 21st Century," by Robert Gilpin.

Skill-Biased Technological Change : Evidence from a Firm-Level Survey - Dubé, Annette (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Skill-Biased Technological Change : Evidence from a Firm-Level Survey," by Donald S. Siegel.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Skilled labor; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Technological change

Canadian Communication Thought: Ten Foundational Writers - Ellerman, Evelyn (Labour / Le Travail, 2001)
The article reviews the book, "Canadian Communication Thought: Ten Foundational Writers," by Robert E. Babe.

Australian Labour History Reconsidered - Farrell, Frank (Labour / Le Travail, 2001)
The article reviews the book, "Australian Labour History Reconsidered," edited by David Palmer, Ross Shanahan, and Martin Shanahan.

The New Prince in a New Principality: OCAP and the Toronto Poor - Feltes, Norman (Labour / Le Travail, 2001)
The article employs Antonio Gramsci's philosophy of praxis to analyze the Ontario Coalition Against Poverty's battle against the proto-fascist, neoconservative Ontario provincial government. A structural diagram, entitled "The Party at the Margin," is presented to show OCAP's place in the current social formation. Adapting Machiavelli, the article considers OCAP's collective "new prince" role, as well as the role of the intellectual. A retired academic, the author was a member of the OCAP executive.

Alabama North: African-American Migrants, Community, and Working-Class Activism in Cleveland, 1915-1945 - Ferguson, Karen (Labour / Le Travail, 2001)
The article reviews the book, "Alabama North: African-American Migrants, Community, and Working-Class Activism in Cleveland, 1915-1945," by Kimberley L. Phillips.

Book Notes [47, Spring 2001] - Finkel, Alvin (Labour / Le Travail, 2001)
The article briefly reviews "Have Women and Minorities Reached the Top? Diversity in the Power Elite," by Richard L. Zweigenhaft and G. William Domhoff; "An Investigation of Racial Disadvantage," by Derek Leslie et al.; Brian Titley's "The Frontier World of Edgar Dewdney;" Gilbert G. Gonzalez's "Mexican Consuls and Labor Organizing: Imperial Politics in the American Southwest;" Peter Bailey's "Popular Culture and Performance in the Victorian City;" Ching Kwan Lee's "Gender and the South China Miracle: Two Worlds of Factory Women;" Diana Crane's "Fashion and its Social Agendas: Class, Gender, and Identity in Clothing;" "Italian Lives: Cape Breton Memories," edited by Sam Migliore and A. Evo Dipierro; and Glenda Riley's "Women and Nature: Saving the 'Wild' West."

Book Notes [48, Fall 2001] - Finkel, Alvin (Labour/Le Travail, 2001)
The article briefly reviews Peter Gossage's "Families in Transition: Industry and Population in Nineteenth Century Saint-Hyacinthe;" Daniel T. Rodgers's "Atlantic Crossings: Social Politics in a Progressive Age;" Claudia Orenstein's "Festive Revolutionaries: The Politics of Popular Theater and the San Francisco Mime Troupe;" Micheal Goldfield's "The Color of Politics: Race and the Mainsprings of American Politics;" Philip Scranton's "Endless Novelty: Specialty Production and American Industrialization, 1865-1925;" "The Living Wage: Building a Fair Economy," by Robert Pollin and Stephanie Luce; Christine Cousins' "Society, Work and Welfare in Europe;" "What Workers Want," by Richard B. Freeman and Joel Rogers; and "On the Front Line: Organization of Work in the Information Economy" by Stephen J. Frenkel, Marek Korczynski, Karen A. Shire, and May Tarn.

The World Guide 2001/2002: An Alternative Reference to the Countries of Our Planet - Finkel, Alvin (Labour / Le Travail, 2001)
The article reviews the book, "The World Guide 2001/2002: An Alternative Reference to the Countries of Our Planet."

CyberUnion: Empowering Labour through Computer Technology - Fiorito, Jack (Relations industrielles / Industrial Relations, 2001)
CyberUnion: Empowering Labor through Computer Technology, by Arthur B. Shostak, is reviewed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; information technology

Connecting Women with Unions: What Are the Issues? - Forrest, Anne (Relations industrielles / Industrial Relations, 2001)
This paper investigates the role of women's issues in the decision to join unions by examining a successful organizing drive in a predominantly female workplace. The main focus of the discussion is the identification of women's issues where they were not immediately apparent to workers and union representatives. The theoretical question raised by this case study is the extent to which women workers' relationship to unions is similar to or different from men workers'. Contemporary industrial relations discourse tends to emphasize the similarities between women and men, without taking into account well-documented differences in women's paid and unpaid work and union experiences. From a feminist perspective, the conclusion that gender is unimportant in organizing campaigns often rests on an inadequate analysis of what constitutes women's workplace/union issues.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Differences; Female employees; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

Laboring for Rights: Unions and Sexual Diversity Across Nations - Forrest, Anne (Relations industrielles / Industrial Relations, 2001)
Laboring for Rights: Unions and Sexual Diversity Across Nations, edited by Gerald Hunt, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Sexuality; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Colliers Across the Sea: A Comparative Study of Class Formation in Scotland and the American Midwest, 1830-1924 - Frank, David (Labour / Le Travail, 2001)
The article reviews the book, "Colliers Across the Sea: A Comparative Study of Class Formation in Scotland and the American Midwest, 1830-1924," by John H. M. Laslett.

Les logiques de la réciprocité. Les transformations de la relation d’assistance aux États-Unis et en France par Sylvie Morel - Freyssinet, Jacques (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Les logiques de la réciprocité. Les transformations de la relation d’assistance aux États-Unis et en France," by Sylvie Morel.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Welfare

Creating and Sustaining Local Union Capabilities: The Role of the National Union - Frost, Ann C. (Relations industrielles / Industrial Relations, 2001)
Drawing on a case study evidence from the automotive, steel, and glass making industries, this article examines the role played by the national union in shaping local unions' abilities to develop and sustain the capabilities critical to managing on-going workplace restructuring. Evidence suggesting the importance of 5 national union characteristics is presented. These characteristics are the breadth of the national union's representational coverage; the extent of its education and training focus on new workplace issues; the resources it devotes to research on the implications of new workplace practices; the presence of multiple communications channels; and its structuring of local union representation.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Corporate reorganization; Labor Unions; Manyindustries; Roles; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

Gender, Segmentation and the Standard Employment Relationship in Canadian Labour Law, Legislation and Policy - Fudge, Judy; Vosko, Leah F. (Economic and Industrial Democracy, 2001)
Using gender as its analytic lens, this article examines segmentation in the Canadian labour market by focusing on the standard employment relationship. It illustrates how standard employment was crafted upon a specific gender division of paid and unpaid labour, the male breadwinner norm, and was only available to a narrow segment of workers. To this end, it traces how from the lOSO's the standard employment relationship was supplemented by a growth in jobs associated with, and filled primarily by, women workers and it shows how women's increasing labour market participation in the late 1960s and early 1970s shaped demands for equality in employment policies. Since the 1980s, a deterioration in the standard employment relationship has undermined both demands for and the basis of gender equality strategies and the article concludes by raising the question of the normative basis for regulating employment in order to move towards strategies for reregulation.

Droit de l’arbitrage de grief, 5e édition - Gagnon, Jean-Denis (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Droit de l’arbitrage de grief," 5e édition, by Rodrigue Blouin and Fernand Morin
Keywords: Arbitration; Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Grievance procedures; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Imagining Internationalism in American and British Labour, 1939-1949 - Gereluk, Winston (Labour / Le Travail, 2001)
The article reviews the book, "Imagining Internationalism in American and British Labor, 1939-49," by Victor Silverman.

Becoming Lean : Inside Stories of U.S. Manufacturers - Gérin-Lajoie, Jean (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Becoming Lean : Inside Stories of U.S. Manufacturers," edited by Jeffrey K. Liker.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Management; Manufacturers; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Learning from Saturn - Gérin-Lajoie, Jean (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Learning from Saturn," by Saul A. Rubinstein and Thomas A. Kochan.
Keywords: AUTOMOBILE industry; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Corporate culture; Corporate profiles; Labor Unions; Labor relations; Labor unions; SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Testing the New Deal: The General Strike of 1934 in the American South - Glaberman, Martin (Labour / Le Travail, 2001)
The article reviews the book, "Testing the New Deal: The General Textile Strike of 1934 in the American South," by Janet Irons.

New Dawn or Bad Moon Rising?: Large Scale Government Administered Workplace Surveys and the Future of Canadian Ir Research - Godard, John (Relations industrielles / Industrial Relations, 2001)
This article discusses the potential advantages of large scale, government administered workplace surveys and the limitations of these surveys in the past. It then reviews and 1995 AWIRS, the 1998 WERS, and the 1999 WES in accordance with how well they appear to have succeeded in overcoming these limitations, and, more generally, with their implications for the conduct of industrial relations research. It is argued that the 1995 AWIRS does not appreciably overcome the limitations of previous surveys.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Business conditions; Employees; Labor Unions; Labor relations; Polls & surveys; R&D; Research; Research & development; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Statistical analysis; Studies

Report of the Advisory Committe on Labour Management Relations in the Federal Public Service, Ottawa, Canada / First Report: Identifying the Issues / L'identification des enjeux / Second Report: Working Together in the Public interest/Travailler ensemble dans l'interet public - Goldenberg, Shirley (Relations industrielles / Industrial Relations, 2001)
Three reports are reviewed: 1. Reports of the Advisory Committee on Labour Management Relations in the Federal Public Service, Ottawa, Canada, 2. First Report: Identifying the Issues, and 3. Second Report: Working Together in the Public Interest.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; Public sector; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Free Trade: Risks and Rewards - Grayson, Kyle (Labour / Le Travail, 2001)
The article reviews the book, "Free Trade: Risks and Rewards," edited by L. Ian MacDonald.

Freedom and Security: An Introduction to the Basic Income Debate - Haddow, Rodney (Labour / Le Travail, 2001)
The article reviews the book, "Freedom and Security: An Introduction to the Basic Income Debate," by Tony Fitzpatrick.

Stations of the Cross: Adorno and Christian Right Radio - Haiven, Judy (Labour / Le Travail, 2001)
The article reviews the book, "Stations of the Cross: Adorno and Christian Right Radio," by Paul Apostolidis.

Health and Work: Critical Perspectives - Haley, Ella (Labour / Le Travail, 2001)
The article reviews the book, "Health and Work: Critical Perspectives," edited by Norma Daykin and Lesley Doyal.

Sur les notions de travail et de citoyenneté à l'heure de la précarité - Hamel, Jacques (Labour / Le Travail, 2001)
The articles traces the genealogy of the idea of work from the perspectives of philosophy, anthropology and sociology. Work is a productive action that also provides the means of existence. Precarious work, however, reveals the limits of this conception. Contrary to the "end of work" thesis, the author argues that work is integral to society, but in a form that does not take the people's labour rights into account, thus undermining their citizenship. This form of integration, which affects young workers especially, can be called "flexploitation." –From author's conclusion

The Erosion of the Country of Origin Effect: A Case Study of a Swedish Multinational Company - Hayden, Annette; Edwards, Tony (Relations industrielles / Industrial Relations, 2001)
Over the last 2 decades, Swedish capital has undergone a rapid internationalization. This has presented a significant challenge to the distinctive nature of the Swedish economy in general and its employment relations system in particular. A key question arising is: to what extent, and in what ways, are Swedish multinationals influenced by the distinctiveness of the country of origin in the way they manager their international workforces? This paper shows how the firm has adopted practices experienced in its foreign operations and deployed these throughout the corporation. The findings are explained with reference to managerial perceptions of the strengths and weaknesses of different "national business systems."
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Corporations; Impact analysis; Labor Unions; Labor relations; Multinational corporations; Rule of origin; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

Ghislain Dufour témoigne des 30 ans du CPQ - Hébert, Gérard (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Ghislain Dufour témoigne des 30 ans du CPQ," by Ghislain Dufour.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Skills Mania: Snakeoil in our Schools? - Heyer, Kent den (Labour / Le Travail, 2001)
The article reviews the book, "Skills Mania: Snakeoil in our Schools?," by Bob Davis.

Italy's Many Diasporas - Hoerder, Dirk (Labour / Le Travail, 2001)
The article reviews the book, "Italy's Many Diasporas," by Donna R. Gabaccia.

Making Reform Happen: The Passage of Canada's Collective-Bargaining Policy, 1943–1944 - Hollander, Taylor (Journal of Policy History, 2001)
Patrick Conroy, the secretary-treasurer of the Canadian Congress of Labour (CCL) from 1941 to 1951, was not someone who gave up easily. As a friend observed, the Scottish-born coal miner was a committed trade unionist whose “moral certitude was admirable and… one of his great strengths.” In late 1942, however, Conroy seemed ready to call it quits on the CCL's campaign to win a national collective-bargaining policy in Canada. Since its inception in September 1940, the Congress, which represented most of the industrial unions in the country, had pushed hard for a comprehensive labor policy like the National Labor Relations or Wagner Act in the United States, which protected and advanced the rights of workers. But the Liberal government of Prime Minister Mackenzie King repeatedly refused to move beyond a turn-of-the-century conciliatory framework that emphasized moral suasion and compromise. In late 1942, when a regional organizer asked Conroy whether a collective-bargaining policy appeared likely in the future, the CCL leader replied: “We do not feel it worthwhile to raise people's hopes when the record of the federal government is as it has been.” –Publisher's extract

The Shadow Welfare State: Labor, Business, and the Politics of Health Care in the United States - Jacobs, David (Relations industrielles / Industrial Relations, 2001)
The Shadow Welfare State: Labor, Business, and the Politics of Health Care in the United States, by Marie Gottschalk, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Health care policy; Labor Unions; Labor relations; Medicare; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

The Great Silent Army of Abolitionism: Ordinary Women in the Antislavery Movement - Kellow, Margaret (Labour / Le Travail, 2001)
The article reviews the book, "The Great Silent Army of Abolitionism: Ordinary Women in the Antislavery Movement," by Julie Roy Jeffrey.

Challenging the Conspiracy of Silence: My Life as a Canadian Gay Activist - Kinsman, Gary (Labour / Le Travail, 2001)
The article reviews the book, "Challenging the Conspiracy of Silence: My Life as a Canadian Gay Activist," by Jim Egan; compiled and edited by Donald W. McLeod.

Off the page and onto the screen - Klausen, Susanne (Labour/Le Travail, 2001)
The author recounts her experience of collaboration on "The Plywood Girls," a video documentary about the hundreds of women who worked at the plywood sawmill in Port Albernini, BC, from 1942 to 1991. Also discusses the difference between working in the print medium (she had previously published an academic article on the subject, based on oral interviews) and visual media (more emotive and transient, but reaches a wider audience).

Creating Competitive Capacity: Labour Market Institutions and Workplace Practices in Germany and the United States - Klikauer, Thomas (Relations industrielles / Industrial Relations, 2001)
Creating Competitive Capacity: Labour Market Institutions and Workplace Practices in Germany and the United States, edited by Peter Berg, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment practices; LABOR market; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

American Science in an Age of Anxiety: Scientists, Anticommunism and the Cold War - Knelman, F. H. (Labour / Le Travail, 2001)
The article reviews the book, "American Science in an Age of Anxiety: Scientists, Anticommunism, and the Cold War," by Jessica Wang.

Striking a Bargain: Work and Industrial Relations in Industrial England, 1815-65 - Koditschek, Theodore (Labour / Le Travail, 2001)
The article reviews the book, "Striking a Bargain: Work and Industrial Relations in Industrial England, 1815-65," by James Jaffe.

Analyse du travail et elaboration des programmes de formation professionelle - Lacombe, Marianne (Relations industrielles / Industrial Relations, 2001)
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Ergonomics; Labor Unions; Occupational training; Participatory research; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Analyse du travail et élaboration des programmes de formation professionnelle - Lacomblez, Marianne (Relations industrielles / Industrial Relations, 2001)
Une approche historique est ici présentée comme démarche permettant de mieux comprendre les options et les enjeux de travaux récents ayant établis des liens privilégiés entre l’analyse du travail et la conception d’action de formation professionnelle. La crise du mode de régulation fordiste semble avoir été déterminante dans l’explosion des recherches et interventions développées ces dernières années dans ce registre. Mais le type de contrat social dans lequel les auteurs se sont inscrits oriente de façon décisive la finalité des projets et la portée des résultats.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les ressources humaines - Laflamme, Roch (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Les ressources humaines," edited by Dimitri Weiss.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Human resources; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Resonable Notice for Wrongful Dismissal: Court Versus Human Resource Decisions - Lam, Helen; Devine, Kay (Relations industrielles / Industrial Relations, 2001)
This study identifies and compares the severance compensation determinants of legal and human resource professionals, using court cases and policy-capturing HR survey. Results confirmed that HR practitioners not only considered the factors critical in court decisions, which were length of service, age, employment status, and labor market conditions, but also had economic and social justice concerns as revealed by significant factors such as a company's financial situation and reason for dismissal. Certain HR decision-makers' characteristics were also found to influence the decision. Overall, HR notices were shorter than court notices in similar situations. Implications of such findings are discussed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Court decisions; Human resource management; Labor Unions; Severance pay; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Wrongful discharge

"The Dresden Story": Racism, Human Rights, and the Jewish Labour Committee of Canada - Lambertson, Ross (Labour / Le Travail, 2001)
This article uses a case study to explore how organized labour, particularly the Jewish Labour Committee, contributed to the development of human rights values and anti-discrimination law in the immediate post-war period. The study focuses on the town of Dresden, Ontario, which at one time was infamous for its treatment of blacks. When a number of organizations (including labour groups) lobbied the Ontario government to create Canada's first Fair Accommodation Practices Act, they pointed to Dresden as an example of why this legislation was necessary. After the legislation was passed, they used litigation to ensure that discrimination in Dresden would come to an end. The paper demonstrates that, although the trade union movement in Canada was not free from racism, it nevertheless played an important and under-appreciated role in fighting for egalitarian human rights.
Keywords: JEWISH Labor Committee (U.S.)

Partenariat, avec ou sans démocratie - Lapointe, Paul-André (Relations industrielles / Industrial Relations, 2001)
Cet article traite des rapports entre le partenariat et la démocratie au travail. Sur la base d’une recherche longitudinale effectuée dans six usines de pâtes et papiers au Québec, nous dressons d’abord un portrait des innovations organisationnelles et de la participation syndicale à la gestion. Nous en dégageons différents cas de figure, incarnant la participation et la démocratie à des degrés très variables. La prise en compte de la dynamique des relations entre acteurs sociaux nous permet ensuite de construire une trajectoire de la participation syndicale à la gestion et de mettre en évidence deux configurations opposées au sein du partenariat, se distinguant selon le caractère de la démocratie salariale et l’évolution du pouvoir syndical.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Partenariat et participation syndicale à la gestion: Le cas de Tembec - Lapointe, Paul-André (Relations industrielles / Industrial Relations, 2001)
Le partenariat n’est susceptible de s’accompagner de la démocratie au travail et d’un renforcement du syndicalisme qu’à certaines conditions et dans certaines circonstances. À défaut de les réunir, se met plutôt en place un processus d’affaiblissement du syndicat local, dans le cadre de dispositifs participatifs sans pouvoir. C’est la principale conclusion qui se dégage de l’étude de Tembec, la plus vieille expérience de partenariat au Québec. En l’absence d’un programme distinctif de celui de la direction, dépourvu de ressources externes et internes et doté d’une démocratie déficiente, le syndicat local s’affaiblit dans le cadre de sa participation à la gestion.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’intervention ergonomique : un regard sur la pratique professionnelle - Ledoux, Élise (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "L’intervention ergonomique : un regard sur la pratique professionnelle," by Fernande Lamonde with the collaboration of Philippe Beaufort.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Négociation collective et régulation du marché du travail en Europe - Leonard, Evelyne (Relations industrielles / Industrial Relations, 2001)
Quel est le rôle de la négociation collective dans la régulation du marché du travail et comment ce rôle évolue-t-il dans le cadre de l’intégration européenne ? Cet article défend l’hypothèse selon laquelle ont récemment émergé dans les pays de l’Union européenne des formes originales de régulation conjointe du marché du travail. Il propose tout d’abord un cadre d’analyse des évolutions récentes en matière de négociations portant sur l’emploi en Europe, avant d’examiner les évolutions nationales. Il met ainsi en évidence la coexistence de divers modes de régulation conjointe du marché du travail dans le contexte européen, pour examiner en finale la nature de cette régulation et ses enjeux pour les relations professionnelles.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Improving the Mastery of Work and the Development of the Work Process in Paper Production - Leppanen, Anneli (Relations industrielles / Industrial Relations, 2001)
The conceptual mastery of the work process and its improvement in the pulp and paper industry has been studied in several mills. Development programs based on systematic analysis and modeling of the work process have been used to improve the work process and the workers' conceptual mastery of it. The participants in the programs have made dozens or even hundreds of concrete proposals to improve the actual work processes and their conceptual mastery of the work process has increased. The results also suggest that conceptual mastery of the work process can be a source of positive well-being. This connection can happen during the development process showing that knowledge of the work process is really valued in the organization.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employees; Labor Unions; Paper industry; Participatory research; Pulp & paper industry; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Training; Work methods improvement

The Woman Worker, 1926-1929 - Lévesque, Andrée (Labour / Le Travail, 2001)
The article reviews the book, "The Woman Worker, 1926-1929," edited by Mararet Hobbs and Joan Sangster.

Quality of Working Life in the Automobile Industry: A Canada-Uk Comparative Study - Lewchuk, Wayne; Stewart, Paul; Yates, Charlotte A. B. (Charlotte Alyce Bronwen) (New Technology, Work and Employment, 2001)
The paper examines the impact of lean production on indicators of the quality of life at work in the automotive industry and finds that it varies across companies and to a lesser extent between countries. The paper explains this by arguing that lean production seeks to impose new employment standards. This is a contested process where management's capacity to shift to new standards and labour's ability to protect its interests vary across workplaces.

Colonizing Bodies: Aboriginal Health and Healing in British Columbia 1900-1950 - Lindberg, Tracey (Labour / Le Travail, 2001)
The article reviews the book, "Colonizing Bodies: Aboriginal Health and Healing in British Columbia, 1900-50," by Mary-Ellen Kelm.

Essential Reading on Race and Law - Lindberg, Tracey (Labour / Le Travail, 2001)
The article reviews and comments on Constance Backhouse's "Colour-Coded Law: A Legal History of Racism in Canada 1900-1950," Sidney L. Harring's "The White Man's Law: Native People in Nineteenth-Century Canadian Jurisprudence,", and James W. St. G. Walker's "'Race,' Rights and the Law in the Supreme Court of Canada."

A Canadian in Lowell: Labour, Manhood and Independence in the Early Industrial Era, 1840-1849 - Little, J. I. (Jack) (Labour / Le Travail, 2001)
The article provides background and publishes a selection of Daniel Spencer Gilman's letters to family members written from the mill town of Lowell, Massachusetts to family members in the Eastern Townships of Lower Canada between 1840 and 1849. The letters provide insight into the meaning of class and gender in Lowell, where the workforce was mostly female. They also indicate that the migration from Lower Canada to the New England mills began earlier than previously suggested.

A Litmus Test for Democracy: The Impact of Ontario Welfare Changes on Single Mothers - Little, Margaret (Studies in Political Economy, 2001)
One of the real litmus tests for the state of our democracy is to examine how we treat the most marginalized. An increasingly demonized and marginalized group in Canadian society is poor single mothers. This article will study the changes to Ontario welfare policy since the election of Premier Mike Harris and the Progressive Conservatives in 1995.
Keywords: Family; Welfare system; Women; Working class

Le métier de préventionniste : contexte de travail et profils d’activités - Loiselle, Claude D.; Bruin, Jean-Pierre (Relations industrielles / Industrial Relations, 2001)
Cet article présente les résultats d’un sondage conduit auprès de préventionnistes représentant l’employeur (n = 111) et de préventionnistes représentant les travailleurs (n = 134) afin de mieux comprendre leurs rôles et leurs fonctions respectives au sein des entreprises. Après une revue de littérature faisant le point sur les dernières connaissances concernant le métier de préventionniste, nous élaborons un cadre théorique permettant deconceptualiser le travail de ces derniers. Les analyses du sondage permettent de faire état des principales caractéristiques du contexte de travail des préventionnistes. Nous décrivons ensuite leurs différents profils permettant de catégoriser leur travail en fonction de trois dimensions (organisationnelle, humaine et technique) et de deux niveaux d’intervention (stratégique et opérationnel).
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Management; Occupational health & safety; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Bibliography: Recent Publications in Canadian Labour History = Bibliographie : Travaux récents en histoire des classes populaires canadiennes [48, Fall 2001] - Lonardo, Michael; Sweeney, Robert C. H. (Labour / Le Travail, 2001)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.

Islands of Truth: The Imperial Fashioning of Vancouver Island - Loo, Tina (Labour / Le Travail, 2001)
The article reviews the book, "Islands of Truth: The Imperial Fashioning of Vancouver Island," by Daniel W. Clayton.

What Kind of Commitment Does a Final-Earnings Pension Plan Elicit? - Luchak, Andrew A.; Gellatly, Ian R. (Relations industrielles / Industrial Relations, 2001)
In a sample of 427 employees in a large, unionized public utility company, the incentive effects of a final-earnings pension plan on employees' commitment to the organization are examined. Two types of organizational commitment, affective and continuance commitment were measured using scales described by Meyer and Allen (1997). Evidence is found that higher accruals under the pension plan increased continuance commitment but reduced affective commitment. Organizational commitment was also found to vary by job satisfaction, specific training, seniority, wage premia, and the perceived effectiveness of alternative dispute resolution methods. Implications for pension theory, research, and policy are discussed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Commitments; Effects; Employee attitude; Incentives; Labor Unions; Pension plans; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

State Regulation and the New Taylorism: The Case of Australian Grocery Warehousing - Lund, John; Wright, Christopher (Relations industrielles / Industrial Relations, 2001)
Studies of the diffusion of new workplace technologies and management practice often fail to account for differences in state labor regulation. This article examines the role of the state in seeking to regulate the introduction of an American system of computerized work monitoring in the Australian grocery warehouse industry. While the establishment of a government inquiry into the technology offered the potential for significant constraints upon management control, over time the state's role shifted to a more accommodating stance that endorsed management's right to use the new technology. The reasons underlying the state's ultimate support for the technology are explored, as are the broader implications for national variations in the global diffusion of new workplace technologies.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Electronic monitoring; Labor Unions; Labor law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; State regulation; Studies; Warehouses

Feminism as a Class Act: Working-Class Feminism and the Women's Movement in Canada - Luxton, Meg (Labour / Le Travail, 2001)
There is a widespread claim that the women's movement of the 1960s and 1970s was middle-class and that its politics of reforming the state reflected the concerns of middle-class women. This paper challenges that claim, arguing instead that the development of the women's movement created an environment in which a union-based, working-class feminism became an important political factor. Working-class and socialist-feminist activists developed a strong feminist presence in the labour movement and a significant working-class orientation in the women's movement that both continue to influence the current women's movement.

Creating Historical Memory: English-Canadian Women and the Work of History - MacDonald, Sharon (Labour / Le Travail, 2001)
The article reviews the book, "Creating Historical Memory: English-Canadian Women and the Work of History," edited by Beverly Boutilier and Alison Prentice.

Pour un modèle renouvelé d’intervention en santé au travail dans les petites entreprises - Marchand, Alain; Simard, Marcel; Ouellet, François; Carpentier-Roy, Marie-Claire (Relations industrielles / Industrial Relations, 2001)
Cet article rapporte les résultats d’une étude de perceptions des interventions en santé au travail dans le contexte des petites entreprises, une réalité qui a jusqu’ici été peu étudiée malgré l’importance de ce type d’entreprise au plans économique et de la santé publique. La méthode a consisté à interroger les travailleurs et les employeurs d’un échantillon raisonné de huit entreprises québécoises de moins de 50 employés, ainsi que les professionnels de la santé chargés d’intervenir dans ces milieux. L’analyse des données permet d’identifier plusieurs aspects problématiques du processus actuel d’intervention en santé au travail dans le contexte de cette catégorie d’entreprise. La portée pratique des résultats est développée en une série de propositions qui visent à renouveler le modèle actuel d’intervention en santé au travail.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Management; Occupational health & safety; Small business; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Heroes and Hallelujahs—Labour History and the Social History of Religion in English Canada: A Response to Bryan Palmer - Marks, Lynne (Histoire sociale/Social History, 2001)
The importance of religion to social and labour radicalism in English Canada has been identified by several scholars, but few labour historians have built on these insights. Some scholars who study labour or socialist leaders at least briefly assess the impact of their subject’s religious background or their relationship to social gospel, while a few historians of working-class ethnic communities explore religion as a facet of their subjects’ lives. Discussion of religion, however, is usually a small part of a larger project. On this theme, Lynne Marks replies to Bryan Palmer’s critique of her book, "Revivals and Roller Rinks: Religion, Leisure and Identity in Late Nineteenth-Century Small-Town Ontario."

News Corporation, Technology and the Workplace: Global Strategies, Local Change - Martin, Roderick (Relations industrielles / Industrial Relations, 2001)
New Corporation, Technology and the Workplace: Global Strategies, Local Change, by Timothy Marjoribanks, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Newspapers; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Technological change

North of the Colour Line: Sleeping Car Porters and the Battle Against Jim Crow on Canadian Rails, 1880-1920 - Mathieu, Sarah-Jane (Saje) (Labour / Le Travail, 2001)
This paper analyzes the evolution of Jim Crow employment patterns in the Canadian railway industry from the 1880s to World War I. It presents race as a central organizing principle in employers' decision to hire black railwaymen for their sleeping and dining car departments. Canadian railway managers actively sought out African American, West Indian, and African Canadian labour, believing that they constituted an easily manipulated group of workers. White railroaders fought the introduction of black employees, arguing that they undermined white manhood and railway unionism. Trade union leaders demanded and won a racialized division of the workforce, locking black workers into low-waged service position when they had initially enjoyed a broader range of employment options. In effect, white railway trade unionists and their employers embraced segregation as a rational model for peaceful working conditions. Black railroaders, on the other hand, resisted the encroachment of segregationist policies by forming their own union, the Order of Sleeping Car Porters. They pressured for change by exposing the scope of Jim Crow practices in the railway industry and trade unionism.
Keywords: Canada; Race; Railroads; Transportation; Unions; Wages

Labour before the Law: The Regulation of Workers' Collective Action in Canada, 1900-1948 - McCallum, Ron (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Labour before the Law: The Regulation of Workers' Collective Action in Canada, 1900-1948," by Judy Fudge and Eric Tucker.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Labor Unions; Labor law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Gérard Hébert: Exemplar of the State of the Art - Meltz, Noah M. (Relations industrielles / Industrial Relations, 2001)
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Us and Them: The Prince Rupert Fishermen's Co-op and Organized Labour, 1931-1989 - Menzies, Charles R. (Labour / Le Travail, 2001)
Cooperative forms of enterprise are often held up as a progressive, moderate alternative to the privations of the capitalist market economy. This paper considers the Prince Rupert Fishermen's Co-op and its relations with organized labour in the north of British Columbia. The paper describes a contradiction within the co-op based on the possibilities of social ownership within a market economy. Through a discussion of the escalating labour conflicts between the co-op and its non-member employees the weaknesses of co-operative enterprises are revealed.

Domestic Goods: The Material, the Moral, and the Economic in the Post-War Years/A History of Domestic Space: Privacy and the Canadian Home - Mezei, Kathy (Labour / Le Travail, 2001)
The article reviews the books, "Domestic Goods: The Material, the Moral, and the Economic in the Post-War Years," by Joy Parr, and "A History of Domestic Space: Privacy and the Canadian Home," by Peter Ward.

Gentlemen Engineers: The Working Lives of Frank and Walter Shanly - Millar, W. P. J. (Labour / Le Travail, 2001)
The article reviews the book, "Gentlemen Engineers: The Working Lives of Frank and Walter Shanly," by Richard White.

Canadian Marxists and the Search for a Third Way - Mitchell, Tom (Labour / Le Travail, 2001)
The article reviews the book, "Canadian Marxists and the Search for a Third Way," by J. Peter Campbell.

Ergonomics, Training and Workplace Change: Introduction - Montreuil, Sylvie; Bellemare, Marie (Relations industrielles / Industrial Relations, 2001)
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Ergonomics; Labor Unions; Occupational training; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Rédaction d’une convention collective : guide d’initiation - Morin, Fernand (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Rédaction d’une convention collective : guide d’initiation," edited by Serge Tremblay.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Citizens and Nation: An Essay on History, Communication and Canada - Morton, Suzanne (Labour / Le Travail, 2001)
The article reviews the book, "Citizens and Nation: An Essay on History, Communication, and Canada," by Gerald Friesen.

Rebel Life: The Life and Times of Robert Gosden, Revolutionary, Mystic, Labour Spy - Mouat, Jeremy (Labour / Le Travail, 2001)
The article reviews the book, "Rebel Life: The Life and Times of Robert Gosden, Revolutionary, Mystic, Labour Spy," by Mark Leier.

Local Unions and Workplace Restructuring: Introduction - Murray, Gregor (Relations industrielles / Industrial Relations, 2001)
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Presentation of the Canadian Industrial Relations Association's Gérard Dion Award to Professor Shirley Goldenberg - Murray, Gregor (Labour / Le Travail, 2001)
The article is the text of the speech given in honour of Shirley Goldenberg as recipient of CIRA's award at its annual conference in 2000.

Syndicats locaux et restructuration des milieux de travail : introduction - Murray, Gregor (Relations industrielles / Industrial Relations, 2001)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Educating Labour's Professionals - Nesbit, Tom (Relations industrielles / Industrial Relations, 2001)
This study examines the nature of education and training for full-time union staff and officials in Canada and explores some of the factors that affect such provision. It was designed to complement similar studies of other countries and to contribute to more general discussions of labor education. The study compares the opportunities of training for Canadian union staff with similar provision in Britain and the US and locates the discussion about further training within the contexts of existing programs of labor education and current debates about the revitalization of the labor movement. The study concludes with a call for more systematic discussion of these issues and analysis of different programmatic models.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Comparative analysis; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Staff; Studies; Training

The World's Strongest Trade Unions: The Scandinavian Labor Movement - Olsen, Gregg M. (Labour / Le Travail, 2001)
The article reviews the book, "The World's Strongest Trade Unions: The Scandinavian Labor Movement," by Walter Galenson.

For Home, Country, and Race: Constructing Gender, Class, and Englishness in the Elementary School, 1880-1914 - Osborne, Ken (Labour / Le Travail, 2001)
The article reviews the book, "For Home, Country, and Race: Constructing Gender, Class, and Englishness in the Elementary School, 1880-1914," by Stephen Heathorn.

Hard Work: The Making of Labor History - Palmer, Bryan D. (Relations industrielles / Industrial Relations, 2001)
Hard Work: The Making of Labor History, by Melvyn Dubofsky, is reviewed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; History; Labor Unions; Labor force; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social classes

Introduction: The Year 2000 and the Deaths of Three Who Made Labour History - Palmer, Bryan D. (Labour / Le Travail, 2001)
The study of he working class and commitment to its causes is central to what this journal is about. Three men who made significant contributions to working class life over the course of the last century, but whose personal efforts, sadly and to our collective loss, came to an end in the year 2000, merit our attention. Marcel Pepin, a vibrant voice in the modern history of Quebec's union movement and former leader of the Confederation of National Trade Unions (CNTU/CSN), died 6 March 2000. ...On 15 June 2000 another advocate of Canadian workers, especially those incarcerated in homelessness and poverty, Norman N. Feltes, died. ...Jack Scott was a revolutionary of the 20th century who had hope for the 21st. He no doubt understood, however, that others would be making history in the new millennium, and his contributions had already been made. He died as the century closed, on 30 December 2000.

Jack Scott, 1910-2000: A Revolutionary Life - Palmer, Bryan D. (Labour / Le Travail, 2001)
The article pays homage to the life and work of Jack Scott.

A Candle For Durruti - Parnaby, Andrew (Labour / Le Travail, 2001)
The article reviews the book, "A Candle For Durruti," by Al Grierson.

Populism - Patten, Steve (Labour / Le Travail, 2001)
The article reviews the book, "Populism," by Paul Taggart.

'Too Well Used by His Master': Judicial Enforcement of Servants' Rights in Montreal, 1830-1845 - Pilarczyk, Ian C. (McGill Law Journal/Revue de droit de McGill, 2001)
The nineteenth century in Montreal was a formative era in the development of modern labour relations. In particular, from 1830 to 1845 the contractual nature of master-servant relations became increasingly apparent, and resort to the local courts as a mechanism for resolving master-servant disputes became commonplace. Master-servant law was comprised of sometimes-competing sources such as notarial contracts and oral agreements, provincial statutes, and municipal bylaws, as well as common law principles and judicial discretion. Other complexities resulted from the discord between the relevant laws governing such relations within the city of Montreal and beyond its limits. Through analysis of primary sources, the author examines the nature and extent of servants rights in the judicial district of Montreal during this period. He devotes particular attention to both the constituent elements of master-servant relations and the most common types of disputes. He begins with an overview of the various forms of nineteenth century labour relations in the Montreal area. Next, he undertakes to elucidate the legal nature of these relations, the roles performed by notaries, and the use of indentures to record the reciprocal contractual obligations of masters and servants. He also considers the differences in master-servant law in the two principal areas of the judicial district of Montreal. Specifically, he considers the types of suits brought within the city of Montreal and beyond its limits and the impact of the different governing laws on their chances of success. Ultimately, servants, through the courts were generally able to protect their rights by bringing suits against their masters for various forms of misconduct.

A World Without War: How US Feminists and Pacifiîts Resisted Workd War I; Women Against the Good War: Conscientious Objection and Gender on the American Home Front, 1941-1947 - Pois, Anne Marie (Labour / Le Travail, 2001)
The article reviews the books, "A World Without War: How US Feminists and Pacifiîts Resisted World War I," by Frances H. Early, and "Women Against the Good War: Conscientious Objection and Gender on the American Home Front. 1941-1947," by Rachel Waitner Goossen.

Working Capital: The Power of Labor's Pensions - Quarter, Jack (Relations industrielles / Industrial Relations, 2001)
Working Capital: The Power of Labor's Pensions, edited by Archon Fung, Tessa Hebb, and Joel Rogers, is reviewed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Pension funds; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social investing

Social Investment by Union-Based Pension Funds and Labour-Sponsored Investment Funds in Canada - Quarter, Jack; Carmichael, Isla; Sousa, Jorge; Elgie, Susan (Relations industrielles / Industrial Relations, 2001)
This study has 2 objectives: 1. to understand the extent of social investment among union-based pension funds as well as labor-sponsored investment funds in Canada, and 2. to understand the factors that affect social investment strategies among such funds. The data indicate that pension funds in Canada have minimal social investment. There is somewhat higher social investment among labor-sponsored investment funds, and particularly labor-sponsored investment funds with genuine union membership. The study also explores factors related to social investment by funds.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Investments; Labor Unions; Labor-sponsored investment funds; Pension funds; Salaries pensions etc; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social investing; Socially responsible investments; Studies; Union membership

The Current Crisis of the South African Labour Movement - Rachleff, Peter (Labour / Le Travail, 2001)
[The article focuses] on a particular conflict in South Africa — the strike this past winter of several thousand Volkswagen workers in Uitenhage, outside of Port Elizabeth, a region known as "the Detroit of South Africa" — and [places] it within the context of a worsening material situation for most South Africans and growing political contusion and tension within the ruling "Triple Alliance" of the African National Congress (ANC), the Confederation of South African Trade Unions (COSATU), and the South African Communist Party (SACP). At this moment, there is an intensifying struggle over privatization and restructuring, a pending battle between pubhc employees and the ANC-run state; and growing enmity between COSATU and the ANC, driven by dissent within COSATU affiliates, over these issues of privatization, the pay of public employees, and a call for the revisions of labour laws in place since 1994, These particular conflicts and the overall situation rest, of course, on South Africa's location within the global economy and the different ways that internal forces are responding to it. In examining these internal forces we can learn more about not only the challenges of economic globalization but also the prospects for challenging it. –From author's introduction

Managing the Multinationals: An International Study of Control Mechanisms - Rees, Chris (Relations industrielles / Industrial Relations, 2001)
Managing the Multinational: An International Study of Control Mechanisms, by Anne-Wil Kathie Harzing, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Management controls; Multinational corporations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Managing Competitive Crisis: Strategic Choice and the Reform of Workrules - Rimmer, Malcolm (Relations industrielles / Industrial Relations, 2001)
Managing Competitive Crisis: Strategic Choice and the Reform of Workrules, by Martyn Wright, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Economic conditions; Economic crisis; Labor Unions; Labor relations; Management decisions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Work rules

Marcel Pepin [1926-2000]: La fidélité, l'affaire de toute une vie - Rioux, Michel (Labour / Le Travail, 2001)
The article pays homage to Marcel Pepin for his lifetime of service and commitment to the labour movement.

Women on the Defensive - Rollings-Magnusson, Sandra (Labour / Le Travail, 2001)
The article reviews the book, "Women on the Defensive: Living through Conservative Times." by Sylvia Bashevkin.

Unionism in Canada and the United States in the 21st century: The prospects for revival - Rose, Joseph B.; Chaison, Gary N. (Relations industrielles / Industrial Relations, 2001)
This paper consider the potential for union revival in Canada and the US. Although unions have devoted considerably energy and resources to new initiatives, the overall evidence leads to generally pessimistic conclusions. The level and direction of union density rates indicates the 2 labor movements lack the institutional frameworks and public policies to achieve sustained revival. Significant gains in union membership and density levels will require nothing less than a paradigm shift in the industrial relations systems - a broadening of the scope and depth of membership recruitment, workplace representation and political activities.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Comparative analysis; International comparisons; Labor Unions; Labor relations; Memberships; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Union membership

Class Action: Reading Labor, Theory and Value - Saraka, Sean (Labour / Le Travail, 2001)
The article reviews the book, "Class Action: Reading Labor, Theory and Value," by William Corlett.

Le temps de travail de ceux qui ne le comptent pas - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Le temps de travail de ceux qui ne le comptent pas," by Bernhard Brunhes Consultants, edited by Danielle Kaisergruber.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

New Paths in Working Time Policy - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2001)
New Paths in Working Time Policy, edited by jean-Yves Boulin and Reiner Hoffmann, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Human resource management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Working hours

The Killing of Karen Silkwood: The Story Behind the Kerr-McGee Plutonium Case - Sass, Robert (Relations industrielles / Industrial Relations, 2001)
The Killing of Karen Silkwood: The Story Behind the Kerr-McGee Plutonium Case, 2nd edition, by Richard Rashke, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Nuclear accidents & safety; Nuclear industry; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Whistleblowing; Working conditions

A Darwinian Left: Politics, Evolution and Cooperation - Schafer, Arthur (Labour / Le Travail, 2001)
The article reviews the book, "A Darwinian Left: Politics, Evolution and Cooperation," by Peter Singer.

Quelques réflexions sur un modèle social européen - Servais, Jean-Michel (Relations industrielles / Industrial Relations, 2001)
L’auteur livre quelques réflexions personnelles sur la spécificité de la réponse européenne à la question sociale telle qu’elle se pose aujourd’hui. Davantage qu’une émanation de la politique de l’Union européenne, il voit dans le modèle social européen un patrimoine commun aux peuples de l’Europe en matière d’emploi et de travail. Ce concept traduit une triple réalité : une régulation sociale fondée sur la concertation ; un régime élaboré de protection sociale et l’existence de services publics à finalité sociale, ainsi qu’un interventionnisme actif de l’État en matières industrielle, économique et sociale. Si ce modèle doit faire face à des critiques et à des difficultés, l’évolution semble davantage aller dans le sens de son adaptation que dans celui de sa disparition.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Globalization and Labour in the Asia Pacific Region - Sharma, Basu (Relations industrielles / Industrial Relations, 2001)
Globalization and Labour in the Asia Pacific Region, edited by Chris Rowley and John Benson, is reviewed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Deregulation; Globalization; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

The Quality of Work: A People-Centred Agenda - Sharpe, Andrew (Relations industrielles / Industrial Relations, 2001)
The Quality of Work: A People-Centred Agenda, by Graham S. Lowe, is reviewed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Job satisfaction; Labor Unions; Labor relations; Quality of work; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social research

Colonial Industrialization and Labor in Korea: The Onoda Cement Factory - Shin, Gi-Wook (Labour / Le Travail, 2001)
The article reviews the book, "Colonial Industrialization and Labor in Korea: The Onoda Cement Factory," by Soon-Won Park.

Economic Conditions and Welfare Reform - Silver, Hilary (Relations industrielles / Industrial Relations, 2001)
Economic Conditions and Welfare Reform, edited by Sheldon H. Danziger, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Economic conditions; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Welfare; Welfare reform

Capital Moves: RCA's 70-Year Quest for Cheap Labor - Sklair, Leslie (Labour / Le Travail, 2001)
The article reviews the book, "Capital Moves: RCA's 70-Year Quest for Cheap Labor," by Jefferson Cowie.

Prometheus Wired: The Hope for Democracy in the Age of Network Technology - Smith, Peter J. (Labour / Le Travail, 2001)
The article reviews the book, "Prometheus Wired: The Hope for Democracy in the Age of Network Technology," by Darin Burney.

Back to the Future: The Contemporary Left and the Politics of Utopia - Soron, Dennis (Labour / Le Travail, 2001)
The article reviews and comments on several books, including "The End of Utopia: Politics and Culture in an Age of Apathy" by Russell Jacoby, "Whose Millennium? Theirs or Ours?" by Daniel Singer, and "Utopistics, Or Historical Choices of the Twenty-first Century," by Immanuel Wallerstein.

Sharing the Work, Sparing the Planet: Work Time, Consumption, and Ecology - Stanford, Jim (Labour / Le Travail, 2001)
The article reviews the book, "Sharing the Work, Sparing the Planet: Work Time, Consumption, and Ecology," by Anders Hayden.

Making the Amalgamated: Gender, Ethnicity, and Class in the Baltimore Clothing Industry, 1899-1939 - Steedman, Mercedes (Labour / Le Travail, 2001)
The article reviews the book, "Making the Amalgamated: Gender, Ethnicity, and Class in the Baltimore Clothing Industry, 1899-1939," by Jo Ann E. Argersinger.

No. 1 Mine: Racism revisited - Stonebanks, Roger; McCallum, Todd (Labour/Le Travail, 2001)
Discusses the anti-Chinese racism surrounding the No. 1 Mine disaster of 1887, when Chinese miners were unfairly blamed for the tragedy. A sign and plaque were unveiled in 1999 at the disaster's site in Nanaimo, BC, where 53 of the 150 miners killed were Chinese.

Challenging Professions: Historical and Contemporary Perpectives on Women's Professional Work - Sugiman, Pamela (Relations industrielles / Industrial Relations, 2001)
Challenging Professions: Historical and Contemporary Perspectives on Women's Professional Work, edited by Elizabeth Smyth, Sandra Acker, Paula Bourne and Alison Prentice, is reviewed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Careers; Female employees; History; Labor Unions; Occupational choice; Professionals; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Privilege and Oppression: The Configuration of Race, Gender, and Class in Southern Ontario Auto Plants, 1939 to 1949 - Sugiman, Pamela (Labour / Le Travail, 2001)
In most studies of the automotive industry in Canada, the workforce has been constructed as uniformly white and male. However, a tiny number of Black men have long had a presence in the industry, occupying the dirtiest, most hazardous, and least desirable jobs in the auto foundries of St. Catharines and Windsor, Ontario. This paper attempts to reconstruct the working lives and union involvements of these men. The paper highlights the themes of racialization and gendering within the sphere of capitalist production. In examining multiple oppressions, simultaneously experienced and resisted, the study furthermore demonstrates the ways in which relations of domination are far more complex and historically-contingent than most analyses of industry and "the auto worker" have suggested.

A Young Man's Benefit: The Independent Order of Odd Fellows and Sickness Insurance in the United States and Canada - Swartz, Donald (Labour / Le Travail, 2001)
The article reviews the book, "A Young Man's Benefit: The Independent Order of Odd Fellows and Sickness Insurance in the United States and Canada, 1860-1929," by George Emery and J. C. Herbert Emery.

Of Moses and Marx: Folk Ideology and Folk History in the Jewish Labor Movement - Taft, Michael (Labour / Le Travail, 2001)
The article reviews the book, "Of Moses and Marx: Folk Ideology and Folk History in the Jewish Labor Movement.," by David Shuldiner.

Shared Earnings, Unequal Responsibilities: Single French-Canadian Wage-Earning Women in Lowell, Massachusetts, 1900-1920 - Takai, Yukari (Labour / Le Travail, 2001)
Lowell, Massachusetts, had a substantial French-Canadian community in the 19th and early 20th centuries. The workforce in the mill town was predominantly female. This study focuses on single French Canadian women in Lowell from 1900 to 1920. The author uses federal census schedules to examine their employment, earnings, and living arrangements. One major finding is that most of the workers were daughters living in households headed by fathers. Housework and family care obligations fell on daughters, which added to their economic responsibilities and reduced their marriageability.

Labouring for Rights: Unions and Sexual Diversity Across Nations - Thomlinson, Neil (Labour / Le Travail, 2001)
The article reviews the book, "Laboring for Rights: Unions and Sexual Diversity Across Nations," edited by Gerald Hunt.

New Rules for a New Economy: Employment and Opportunity in Post-Industrial America - Timur, A. Tarik (Relations industrielles / Industrial Relations, 2001)
New Rules for a New Economy: Employment and Opportunity in Post-Industrial America, by Stephen A. Herzenberg, John A. Alic, and Howard Wial is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment; Labor Unions; Labor relations; Service industries; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Les nouvelles frontières de l’inégalité : hommes et femmes sur le marché du travail - Tremblay, Diane-Gabrielle (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Les nouvelles frontières de l’inégalité : hommes et femmes sur le marché du travail," edited by Margaret Maruani.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Hommage à Gérard Hébert (1921-2001) - Trudeau, Gilles (Relations industrielles / Industrial Relations, 2001)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Droit des relations de travail en Amérique du Nord - Verge, Pierre (Relations industrielles / Industrial Relations, 2001)
The article reviews the book,. "Droit des relations de travail en Amérique du Nord," by Kevin Banks, Lance Compa, Leoncio Lara and Sandra Polaski.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Rise and Development of Collective Labour Law - Verge, Pierre (Relations industrielles / Industrial Relations, 2001)
This article reviews the book, "The Rise and Development of Collective Labour Law," edited by Marcel van der Linden et Richard Price.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Participatory Ergonomics Training in the Manufacturing Sector and Ergonomic Analysis Tools - Vincent, Marie St; Lortie, Monique; Chicoine, Denise (Relations industrielles / Industrial Relations, 2001)
This article discusses the importance of job analysis tools for training in the context of participatory ergonomic processes. It explains the major principles and challenges in the design of these tools for short-cycle repetitive tasks and for long-cycle varied tasks. The intervention framework is described and the proposed tools are presented and related to the literature. The participants' difficulties with the tools developed in both contexts studied are summarized. The discussion suggests that these difficulties are partly related to the company context and raises questions about the data relevant for the evaluation of solutions in the case of non-repetitive tasks.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Ergonomics; Injuries; Job analysis; Labor Unions; Manufacturing; Musculoskeletal system; Occupational health & safety; Participatory research; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Training

Obligation and Opportunity: Single Maritime Women in Boston, 1870-1930 - Waldron, Florence Mae (Labour / Le Travail, 2001)
The article reviews the book, "Obligation and Opportunity: Single Maritime Women in Boston, 1870-1930," by Betsey Beattie.

The Arthur Webb Story 1885-1964 - Webb, Jeff A. (Labour / Le Travail, 2001)
Written in the early 1960s and published for the first time in Labour/Le Travail, this memoir is of interest to labour historians for its portrayal of a working-class immigrant's life. The article introduces the autobiography of Arthur Webb, who in 1901 at age 16 emigrated from the UK to Canada. Webb reminisces about his childhood years in Liverpool (he began working at age 10 and had little formal education), then describes the series of temp jobs he held as a farm hand and labourer after his arrival in rural New Brunswick. He was a soldier before and during the First World War (he was gassed at Ypres) and latterly became a firefighter in Saskatoon, retiring in 1943 due to medical unfitness. He was deeply affected by the death of his wife in 1954, but remained determined to carry on - a recurring theme.

Labour Markets, Flexible Specialization and the New Microcorporatism: The Case of Canada's Major Appliance Industry - Wells, Don (Relations industrielles / Industrial Relations, 2001)
"High performance" management systems in unionized workplaces have the potential to create a more microcorporatist workplaces have the potential to create a more microcorporatist industry relations system in Canada. Microcorporatist tendencies reflect more active worker cooperation in achieving management productivity, quality and flexibility goals. Analysis of development of these tendencies in the major appliance industry suggests that microcorporatism has contradictory implications. In one direction lies the displacement labor politics by a local-centered unionism that is increasingly captured by the logic of market competition. In a second direction lies a logic of greater worker resistance related to increased worker control of labor processes.
Keywords: Appliance industry; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; LABOR market; Labor Unions; Labor relations; Management styles; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

Dreamworld and Catastrophe: The Passing of Mass Utopia in East and West - Wernick, Andrew (Labour / Le Travail, 2001)
The article reviews the book, "Dreamworld and Catastrophe: The Passing of Mass Utopia in East and West," by Susan Buck-Morss.

L’éclatement de l’emploi traditionnel : les défis posés par la diversité des emplois typiques et atypiques - Wils, Thierry; Bourhis, Anne (Relations industrielles / Industrial Relations, 2001)
L’emploi traditionnel éclate de plus en plus pour donner naissance à une grande diversité d’emplois atypiques. Ce nouveau phénomène, qui est encore mal connu, pose de nombreux défis tant aux gestionnaires qu’aux travailleurs et à la société. Un des problèmes majeurs pour gérer ces enjeux est la difficulté de cerner adéquatement l’ampleur et la nature des transformations actuelles parce que les différentes formes de travail atypique n’ont pas encore été clairement définies. La contribution de cet article est de clarifier les différentes formes de travail à l’aide de deux typologies, une typologie des formes de travail et une typologie des travailleurs. L’étude révèle que plusieurs défis importants posés par cette nouvelle réalité dépendent à la fois de la forme de travail atypique concernée et des caractéristiques des travailleurs.
Keywords: Alternative work arrangements; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

"Heal Thyself" Managing Health Care Reform - Wilson, Donna (Labour / Le Travail, 2001)
The article reviews the book, "'Heal Thyself': Managing Health Care Reform," by Pat Armstrong, Hugh Armstrong, Ivy Lynne Bourgeault, Jacqueline Choiniere, and Eric Mykhalouskiy.

The Future of Social Democracy: Views of Leaders From Around the World - Wiseman, Nelson (Labour / Le Travail, 2001)
The article reviews the book, "The Future of Social Democracy: Views of Leaders From Around the World," edited by Peter H. Russell.

Class Difference and the Reformation of Ontario Public Hospitals, 1900-1935: "Make Every Effort to Satisfy the Tastes of the Well-to-Do." - Wishart, James M. (Labour / Le Travail, 2001)
At the beginning of the 20th century, charity hospital governors in Ontario began to explore the possibility of admitting paying patients to help offset the costs of providing medical charity. This transformation entailed changes in administration, as well as concerted publicity and marketing campaigns to rehabilitate the image of the hospital and to attract affluent health consumers. The subsequent construction of new hospital facilities, exclusively for the use of paying customers, was informed by an ideology that mandated the physical separation of social classes and the identification of deserving and less deserving recipients of health care services. This paper examines aspects of the design, management, marketing, and staffing of a number of southern Ontario public hospitals to illustrate how the transformation of these institutions in the years between 1900-1935 actively shaped class inequality within and outside their walls.

South African Trade Unions in a Time of Adjustment - Wood, Geoffrey (Labour / Le Travail, 2001)
The paper examines South African trade unions from the late apartheid era to the present (2001). Anti-apartheid sanctions and disinvestment affected the labour movement, as did the disastrous miners' strike of 1987. Democratization in the period since has resulted in the lifting of embargoes and the phasing-out of tariffs and state subsidies for industries located near the former bantustans. There has been a growth of public sector unions and private sector unions have also reversed their decline. Generally, the unions are still a force to be reckened with, but the neoliberal turn of the ruling African National Congress, to which the unions are closely linked, poses a serious challenge.

Endless Propaganda: The Advertising of Public Goods - Wright, Cynthia (Labour / Le Travail, 2001)
The article reviews the book, "Endless Propaganda: The Advertising of Public Goods," by Paul Rutherford.

"Ringing in the Common Love of Good": The United Farmers of Ontario, 1914-1926 - Wylie, Robin (Labour / Le Travail, 2001)
The article reviews the book, "Ringing in the Common Love of Good: The United Farmers of Ontario, 1914-1926," by Kerry A. Badgley.

Allies Across the Border: Mexico's "Authentic Labour Front" and Global Solidarity - Zapata, Francisco (Relations industrielles / Industrial Relations, 2001)
Allies across the Border: Mexico's "Authentic Labour Front" and Global Solidarity, by Dale Hathaway, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor; Labor Unions; North American Free Trade Agreement; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z